Design of an earthdam on river Tochi in Dobi LC (II) Zone in Omoro c ounty; Gulu District - Okumu, Edward (Kampala: Makerere University, 1997)
Dissertation (B.Sc., Agric.Eng.) - Makerere University, 1997
Includes bibliographical references (p.78)
Keywords: Earth dams -- Design and construction -- Uganda -- Gulu District